Analysis and investigation of different advanced control strategies for high-performance induction motor drives - Nabil Farah; M. H. N. Talib; Z. Ibrahim; Qazwan Abdullah; Ömer Aydoğdu; Zulhani Rasin; Auzani Jidin; Jurifa Mat Lazi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Induction motor (IM) drives have received a strong interest from researchers and industry particularly for high-performance AC drives through vector control method. With the advancement in power electronics and digital signal processing(DSP), high capability processors allow the implementation of advanced control techniques for motor drives such as model predictive control (MPC). In this paper, design, analysis and investigation of two different MPC techniques applied to IM drives; themodel predictive torque control (MPTC) and model predictive current control (MPCC) are presented. The two techniques are designed in Matlab/Simulink environment and compared interm of operation in different operating conditions. Moreover, a comparisonof these techniques with field-oriented control (FOC) and direct torque control (DTC) is conducted based on simulation studies with PI speed controller for all control techniques. Based on the analysis, the MPC techniques demonstrates a better result compared with the FOC and DTC in terms of speed, torque and current responses in transient and steady-state conditions.